Hubungan Pengetahuan Ibu Mengenai Pemberian Asi Terhadap Status Gizi Bayi Usia 6-24 Bulan Di Kelurahan Semanggi, Kecamatan Pasar Kliwon, Kota Surakarta - Prasetyo, Bayu; Muwakhidah, Muwakhidah.,SKM, M.Kes, Nur lathifah Mardiyati, S., M>SGz (2016)
Introduction. Given malnutrition is highest in clover village that is equal to 3.6% and the knowledge of mothers on breastfeeding were also lacking with a high prevalence of 45%, it encourages researchers to analyze the relationship between maternal knowledge about breastfeeding on the nutritional status of infants aged 6-24 months in Semanggi Village, Pasar Kliwon, Surakarta city. Objective. To determine whether there is relationship between maternal knowledge about breastfeeding on the nutritional status of infants aged 6-24 months in,Semanggi Village, Pasar Kliwon, Surakarta city. Research methods. This type of research using cross sectional method which researchers took the data of independent variables and the dependent variable in the same time period. This research was descriptive and analytical observational. This study measured the level of knowledge of mothers on breastfeeding and measurement of nutritional status in children aged,6-24,months,in,Semanggi Village,Pasar.Kliwon,Surakarta. The sampling technique using random sampling method. by way of direct interviews with the help of the data registers nutritional status of infants and toddlers. Analysis relationships using Spearman Rank Correlation Test. Results. Good knowledge about breastfeeding at 18 respondents with a percentage of 25%, and mothers who have the knowledge is still lacking by 54 respondents with a percentage of 75%. Of the 72 children under five respondents, 9 underweight children is the percentage of 12.50%, 56 stunting normal with a percentage of 77.77%, 3 stunting with a percentage of 4.18%, 4 children malnutrition by 5 percentage , 55%. Results of testing the hypothesis with Spearman Rank correlation values obtained significant p value 0.206 (0.206> 0.05). Conclusion. There was no association between maternal knowledge about breastfeeding on the.nutritional,status.in.Clover,Village,,Pasar.Kliwon,.Surakarta. Suggestion. Can provide educational information about nutrition and provide nutrition program to address nutritional problems occur. Keywords : Knowledge mother, breastfeeding, nutritional status, Infants aged 6-24 months, Village Semanggi